Risk identification guarantee and flexible coordination of heterogeneous energy systems in Northeast China under extreme conditions - Tao Meng; Hongpeng Liu; Yong Sun (International Journal of Electrical Power & Energy Systems, 2025)
Aiming at the impact of extreme conditions on the new power system in Northeast China, risk operation characteristics of electricity-gas-heat heterogeneous energy system are studied. Firstly, flexible resources are explored to participate in the heterogeneous energy flow interaction. Risk resistance system is proposed, which includes three parts: the risk identification of the source-load side, the identification of the weak links in network, the risk power supply guarantee strategy. Then, flexible collaborative stratification model is established to achieve analysis and regulation of risk operation. Finally, a heterogeneous energy system in the Northeast city of China is simulated. Various coordinated schemes for risk scenarios are studied, and the safety, flexibility, stability and economy are evaluated. The results show that risks can be quantitatively evaluated through the risk identification of the source-load side. Differential power supply guarantee states can be divided through the identification index of weak links. Various regulation schemes can be formulated through the risk power supply guarantee strategy. In addition, regulatory effects can be improved with flexible resources and low-carbon units. The operation stability and energy complementarity in risk scenarios can be effectively enhanced. Thereby, the rationality and effectiveness of method proposed in this paper are verified.